مدى امتلاك أعضاء هيئة التدريس بقسم المحاسبة بجامعة بنغازي لمهارات ومعارف تكنولوجيا المعلومات اللازمة لتطوير التعليم المحاسبي - المنصوري فادية سعد خليفة (Scientific Journal of University of Benghazi, 2022)
The study aimed to know and identify the degree to which the faculty members of the Accounting Department at the University of Benghazi possess the skills and knowledge of information technology necessary for the development of accounting education. The study population was represented by all 63 faculty members of the Accounting Department of the University of Benghazi. The questionnaire was used as a data collection tool to achieve the objectives of the study, and the data were analyzed using statistical software packages (SPSS), and descriptive statistical methods were used to represent the arithmetic mean and standard deviation. The results of the study concluded that faculty members of the Accounting Department do not have the skills required for using and dealing with modern educational devices nor do they have knowledge of computer software. However, the Accounting Department faculty members possess a high degree of skills in internet technology. The study recommends enhancing awareness and informational culture for faculty members, developing their skills and training them on how to employ information technology as well as adopting modern technologies for developing accounting curricula.